Implementasi Pembelajaran IPA untuk Membangun Karakter Religius Siswa di Kelas V MI Nurul Ulum Pegiringan - Rifki Nuriza (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
The implementation of science learning in schools not only aims to improve students' academic understanding, but also plays an important role in building religious character. Research shows that the integration of religious values in science learning can strengthen students' belief in religious teachings and increase their positive behavior. For example, Islamic values integrated into science materials at the SD/MI level can encourage students to be more convinced of the existence of Allah and follow His provisions, thus forming a strong religious character. In addition, learning approaches that prioritize routine activities such as praying together and reading the Qur'an before lessons have also proven effective in instilling religious character. Furthermore, the application of learning modules that integrate basic concepts of science with Islamic values, such as those conducted at the University of KH Abdurrahman Wahid Pekalongan, shows that students can better understand the material while internalizing religious values in their daily lives. Other studies also emphasize the importance of character education programs integrated in the curriculum, where religious activities at school, such as congregational prayers and holiday celebrations, contribute significantly to the formation of students' religious character. Thus, well-designed science learning can be an effective means to build students' religious character.